2005
DOI: 10.1007/s00276-005-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the nerves entering into the coracobrachialis muscle

Abstract: The nerves entering into the coracobrachialis muscle are the musculocutaneous nerve (MC) and the nerve (usually consists of several thin branches) branches to the coracobrachialis. These thin branches enter the coracobrachialis proximal to the MC. The thin branches and the MC are susceptible to injury during coracoid process transfer. The purpose of this study is (1) to reveal the number and origin of the thin branches and (2) especially to report the morphometric information about the two distances between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Different courses and relations of the MCN within coracobrachialis have been reported. Ozturk et al (2005) observed that the MCN entered coracobrachialis in all 42 upper limbs they studied, whereas Eglseder and Goldman (1997) and Pacha Vicente et al (2005) reported that the MCN did not pierce coracobrachialis in 29.6% and 6.5% of the specimens, respectively. Macchi et al (2007) also noted large variability in the point of entry of the MCN, which was associated with a low variation in the exit point from coracobrachialis and that the latter was positively correlated to the length of the muscle.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Different courses and relations of the MCN within coracobrachialis have been reported. Ozturk et al (2005) observed that the MCN entered coracobrachialis in all 42 upper limbs they studied, whereas Eglseder and Goldman (1997) and Pacha Vicente et al (2005) reported that the MCN did not pierce coracobrachialis in 29.6% and 6.5% of the specimens, respectively. Macchi et al (2007) also noted large variability in the point of entry of the MCN, which was associated with a low variation in the exit point from coracobrachialis and that the latter was positively correlated to the length of the muscle.…”
Section: Discussionmentioning
confidence: 88%
“…Helfet (1958) recognized the clinical significance of a high entry of the MCN into coracobrachialis. Subsequently, several investigators have suggested that the entry point of the MCN into coracobrachialis is clinically important, with a correlation between high entry points and frequency of nerve injuries being reported (Flatow et al, 1989;Ozturk et al, 2005;Macchi et al, 2007). Some studies have reported cases in which the MCN does not pierce cor-acobrachialis, in which case a direct branch from lateral cord of the brachial plexus was observed to supply the muscle (Eglseder and Goldman, 1997;Venieratos and Anagnostopoulou, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…The studies and the reported percentages of the specimens, which the MCN did not pierce coracobrachialis, are as follows: Eglseder and Goldman (1997) 29.6%, Choi et al (2002) Ozturk et al (2005) reported that in all 42 extremities, the MCN had no variations, originated from the lateral cord of the brachial plexus and entered the coracobrachialis. Uysal et al (2009) reported that the MCN entered the superior part of coracobrachialis in 43% of specimens, the middle part in 37%, and the inferior part in 17%.…”
Section: Discussionmentioning
confidence: 97%
“…Kerr (1918) reported that these branches arose from the MCN in 54 out of the 109 plexuses. Ozturk et al (2005) found these branches from MCN to the coracobrachialis in all 42 extremities. MCN has been studied in several studies, but in most of them, these branches have not been mentioned.…”
Section: Discussionmentioning
confidence: 97%
“…Although there are several reports on variations in the origin and distribution of the nerve the spinal root composition of the nerve itself has not been thoroughly investigated in past literature (4,5,9).…”
Section: Resultsmentioning
confidence: 99%